Influence of CH4 hydrate exploitation using depressurization and replacement methods on mechanical strength of hydrate-bearing sediment - Lee, Yohan; Deusner, Christian; Kossel, Elke; Choi, Wonjung; Seo, Yongwon; Haeckel, Matthias (Applied energy, 2020)
[Display omitted] •The effects of the combined method on HBS geomechanical properties were examined.•Mechanical behavior depended on dissociation ratios and GH saturations.•Mechanical strength of the replaced HBSs was significantly recovered.•The combination of depressurization and replacement increased total CH4 recovery.•Optimum replacement occurred at a dissociation ratio of 20% with CO2 injection. This study analyzed the potential effects of gas hydrate (GH) exploitation on the geomechanical properties of hydrate-bearing sediment (HBS) by examining the combined effects of depressurization and CO2 injection using triaxial compression tests. The stress-strain behavior of the initial CH4 HBS showed strong hardening-softening characteristics and high peak strength, whereas milder hardening-softening behavior and reduced peak strength were observed after partial (20, 40, 60, and 80%) or complete GH dissociation (100%), indicating that the mechanical behavior clearly depended on dissociation ratios and GH saturations. In response to CO2 injection in partially dissociated HBS, subsequent CH4–CO2 hydrate exchange, and secondary CO2 hydrate formation, the mechanical strength of the replaced HBS recovered significantly, and stress-strain characteristics were similar to that of the 20% dissociated CH4 HBS. Although total CH4 recovery was increased by the combination of depressurization and replacement, optimum recovery was found at a dissociation ratio of 20% followed by replacement because production by replacement decreased as the dissociation ratio increased. These results contribute to the understanding of how depressurization and CO2 injection schemes may be combined to optimize energy recovery and CO2 sequestration. In particular, this research demonstrates that CH4–CO2 hydrate exchange and secondary GH formation are suitable methods for controlling and maintaining the mechanical stability of HBSs.